POMbranes: polyoxometalate-functionalized block copolymer membranes for oxidation catalysis. Issue 30 (21st July 2017) - Romanenko, I.; Lechner, M.; Wendler, F.; Hörenz, C.; Streb, C.; Schacher, F. H.
Abstract : The immobilization of homogeneous catalysts within nanoporous membranes gives access to catalytically active and multi-functional composite materials, e.g. for use in flow reactors. Abstract : The immobilization of homogeneous catalysts within nanoporous membranes gives access to multi-functional composites, e.g. for use in flow reactors. Here, we report the fabrication of catalytically active porous block copolymer membranes prepared via non-solvent induced phase separation of amphiphilic block copolymers. Keggin-type polyoxometalates (POMs) [PV2 Mo10 O40 ] 5− were immoblilized on the membrane by electrostatic interactions between the POM anions and the cationic surface charges of the hydrophilic poly(amino methacrylate) units. Morphological studies show that the original pore structure is retained in the functionalized hybrid membranes and the POMs are homogeneously distributed on the pore walls. The membranes were employed as heterogeneous composites for liquid-phase substrate oxidation with a focus on the oxidation of anthracene to anthraquinone and tetrahydrothiophene to tetrahydrothiophene oxide. The membranes show promising catalytic activity, can be re-used several times and deployed in prototype flow reactors. The results therefore demonstrate how highly tunable POM catalysts can be heterogenized on nanostructured block copolymer membranes, leading to advanced composite catalysts with potential relevance for industrial oxidation catalysis.